Analysis of Expressive Speech Acts in FWB Novel Pia Davina's Work - Helmi Seftiani; Sigit Andi Prasetya Dinata; Diana Diana (International Journal of Science and Applied Science: Conference Series, 2021)
This research tries to  describe the forms  of expressive speech acts found in Pia Davina's novel "Friends with Bittersweet Love" (FWB). This research use desciptive qualitative approach. The expressive speech acts found in the FWB novel "Friends with Bittersweet Love" by Pia Davina are the data source for this research. To collect data, documentation techniques, namely note-taking techniques, are used to discover and record various styles of expression found in new texts. It is hoped that this research can increase our understanding of how novel characters use language to express their feelings and emotions, as well as how expressive speech acts contribute to the development of story lines and characters.